Benefits of Mixtures on Growth Performance of Silver Fir (Abies alba) and European Beech (Fagus sylvatica) Increase With Tree Size Without Reducing Drought Tolerance - Schwarz, Julia A.; Bauhus, Jürgen (Frontiers in Forests and Global Change, 2019)
To mitigate negative impacts of drought stress in the face of climate change, mixtures of tree species such as those between European beech (Fagus sylvatica) and silver fir (Abies alba) are assumed to lower risks in forest management. This study investigates the influence of mixing beech and fir on tree growth in general and in particular on tree species responses to the extreme drought event of 2003. For this purpose, we analyzed basal area increment series and carbon isotope composition (δ13C) in the wood of ~160 trees from three mixed-species sites in Germany and one site in Croatia. Overall growth performance for both fir and beech increased with proportions of the admixed species when accounting for the interactions with tree size and competition intensity. Mixing improved growth of large trees for both species irrespective of neighborhood density, whereas smaller trees benefitted only in denser neighborhoods. Positive mixing effects on radial growth were more pronounced in fir compared to beech, yet the latter benefitted by the admixture of fir with regard to growth recovery following drought. Both the resistance of radial growth against reduction during drought as well as the variation of isotopic composition throughout the drought period were not affected by mixing, indicating that water-use in these two species was not complementary under drought stress. Although trees from both species exhibited growth reductions during the drought, fir maintained higher absolute growth levels than beech during the drought. Both species benefited from growing in mixed neighborhoods but complementary effects depended on tree size and neighborhood density. Mixing fir and beech leads to positive or neutral effects on growth performance of trees, also in response to an extreme drought event. Since increasing tree species richness also spreads the risks associated with extreme events, mixtures of beech and fir can be recommended as a possible alternative for more drought-sensitive stands such as spruce monocultures.